Eksistensi Public Relations (Hubungan Masyarakat) pada suatu Perusahaan (Suatu Tinjauan Public Relations dalam Perspektif Komunikasi) - Mardhiah, Ainol (Universitas Brawijaya, Indonesia, 2008)
Talking about Public Relations iis means that talking one dimension of communications sciences. Public relations consist of all forms of planned communications, outwards and inwards, between an organizations and its publics for the purposes of achieving specific objectives concerning mutual understanding. There are two subject or public that needed to attence by public relations officer, they are internal public relations and exsternal public relations. Public Relations is the mediator between the public and the firms, so the communication that happened in public relations in a firm must be two way communication (mutual understanding). The most important thing public relations officer has to able create something good to achaive the aim by create public understanding, public confidence, public support and public cooperations.